PENGARUH STORE ATMOSPHERE DAN KUALITAS PELAYANAN TERHADAP NILAI PELANGGAN COFFE SHOP DI KOTA SOLO - Masril Rya; Euis Eka Pramiarsih (Holistik Manajemen: Jurnal Manajemen, 2020)
The fairly good economic conditions then stimulated entrepreneurs to invest, especially in modern industries. One of the cafe and restaurant businesses that are currently popping up is a cafe with a coffee shop concept or coffee shop. One aspect that is used by the public as a customer in choosing a place to enjoy coffee is by comparing the value received by the customer (customer value). However, now customers also tend to choose places to carry out their consumption activities. The factors of the place are part of the store atmosphere. Customer assessment also relates to the quality of service or service quality provided. The purpose of this study is to determine the effect of store atmosphere on customer value, the effect of service quality on customer value, and to know the effect of store atmosphere and service quality on customer value. This research uses quantitative descriptive research. The number of samples used in this study were 100 samples. The data analysis technique used in this study was SEM-PLS. The results showed that the results of the t test obtained a value of tcount (3.373)> t table (1.96), so that it could be said that there was a significant influence on the Store atmosphereter towards the Value of the customer. The results of the t test obtained a value of tcount (2.716)> ttable (1.96), so that it can be said that there is a significant effect of service quality on customer value and the value of R square for customer value of 0.519. This shows that the customer value variable can be influenced by the Store Atmosphere and Service Quality variables with a magnitude of influence of 51.9%. Suggestions in this study are Store atmosphere and service quality needs to be maintained and continuously improved because it will have an impact on customer value, future research should use different samples and from different organizations, and further researchers are expected to be able to examine with other variables outside variables that have been studied so that they can obtain more varied results that can affect customer value.